Language in the world : a philosophical enquiry - Cresswell, M. J. (Cambridge University Press, 1994)
What makes the words we speak mean what they do? Possible-worlds semantics articulates the view that the meanings of words contribute to determining, for each sentence, which possible worlds would make the sentence true, and which would make it false. M. J. Cresswell argues that the non-semantic facts on which such semantic facts supervene are facts about the causal interactions between the linguistic behaviour of speakers and the facts in the world that they are speaking about, and that the kind of causation involved is best analysed using David Lewis's account of causation in terms of counterfactuals. Although philosophers have worked on the question of the connection between meaning and linguistic behaviour, it has mostly been without regard to the work done in possible-world semantics and Language in the World is a book-length examination of this problem.